A combined laboratory and field evaluation of the Cholestech LDX and CardioChek PA point-of-care testing lipid and glucose analysers. (January 2014) - Whitehead, Simon J; Ford, Clare; Gama, Rousseau
Background: Combined lipid and glucose point-of-care testing (POCT) devices could facilitate widespread population screening for cardiovascular disease (CVD) and diabetes as part of the NHS Vascular Risk Assessment and Management Program (NHS Health Checks). An evaluation of the Cholestech LDX and CardioChek PA POCT analysers was performed in collaboration with the Wolverhampton City Primary Care Trust (PCT). Methods: Intra-/inter-batch imprecision, between-analyser variation and the effect of haematocrit and ascorbic acid assay interference were investigated. Accuracy of the POCT capillary whole blood total cholesterol (TC), high-density-lipoprotein cholesterol (HDL-C) and glucose measurements was estimated by comparison with those from the laboratory analysis of paired venous samples. POCT usability and clinical governance were also assessed. Results: The LDX exhibited lower intra- and inter-batch imprecision and external quality assessment (EQA) scheme between-analyser variation for the measurement of TC, HDL-C and glucose when compared to the CardioChek. Ascorbic acid negatively interfered in all three assays on both POCT analysers and results reported by the CardioChek were influenced by the specimen haematocrit. The LDX displayed closer agreement with the laboratory methods for the measurement of TC and HDL-C but both the LDX and the CardioChek displayed positive bias for the measurement of glucose. Conclusions: POCT has clear advantages for delivering NHS Health Checks over the laboratory-based approach although device performance does differ. Users should also be aware of the potential clinical governance and interference issues associated with these devices.